Anchors Weigh More Than Power: Why Absolute Powerlessness Liberates Negotiators to Achieve Better Outcomes. (February 2015) - Schaerer, Michael; Swaab, Roderick I.; Galinsky, Adam D.
The current research shows that having no power can be better than having a little power. Negotiators prefer having some power (weak negotiation alternatives) to having no power (no alternatives). We challenge this belief that having any alternative is beneficial by demonstrating that weak alternatives create low anchors that reduce the value of first offers. In contrast, having no alternatives is liberating because there is no anchor to weigh down first offers. In our experiments, negotiators with no alternatives felt less powerful but made higher first offers and secured superior outcomes compared with negotiators who had weak alternatives. We established the role of anchoring through mediation by first offers and through moderation by showing that weak alternatives no longer led to worse outcomes when negotiators focused on a countervailing anchor or when negotiators faced an opponent with a strong alternative. These results demonstrate that anchors can have larger effects than feelings of power. Absolute powerlessness can be psychologically liberating.